Analisis Kinerja Keuangan Sebelum dan Sesudah Merger dan Akuisisi pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2020-2022 - Mohammad Egi Safruddin; Wulan Suryandani (Al-Buhuts, 2026)
This study aims to analyze the differences in financial performance before and after mergers and acquisitions in companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The sample in this study consisted of 29 companies selected using a purposive sampling technique based on predetermined criteria that align with the research objectives. The method used was a quantitative approach by applying the Wilcoxon signed rank test because all data were proven to be non-normally distributed. Financial performance indicators used in this study include Current Ratio (CR), Total Asset Turnover (TATO), Return on Assets (ROA), and Return on Equity (ROE), each of which represents aspects of liquidity, activity, and company profitability. The results of the study based on descriptive analysis show that several variables experienced an increase in financial performance in the two years before and two years after the merger and acquisition activities, while the results of the Wilcoxon Signed Rank Test indicate that there is no significant difference in financial performance in all these variables between the two years before and two years after the merger and acquisition activities. Thus, the merger and acquisition activities during the research period have not been able to provide significant changes to the company's financial condition in the short term. This finding indicates that the merger and acquisition strategy has not optimally produced the expected financial synergies, so that improving financial performance may take a longer time.